An Assessment of Cleanliness Level from Service Level Agreement and User’s Perception in Universiti Tun Hussein Onn Malaysia - Ishak, Mohd Hafizal; Mohd Anasir, Nurul Najihah (Research in Management of Technology and Business, 2020)
Cleanliness in the building creates a perfect living, learning and working environment. To achieve high standards cleanliness, a facilities manager needs to have a good service level agreement (SLA) between the service provider and service recipient. In the university context, an increased number of students has created challenges for the cleaning service provider to provide quality services. On top of that, the facilities management (FM) department has to be sensitive with the budgetary and cost. Hence, balancing between costs, services and meeting the user expectations are the most important elements in managing cleanliness for university buildings. Aim of this research is to assess the cleanliness level from the SLA and user perception. Two objectives were set, first is to identify the elements used in the SLA for building cleaning in the university and second is to analyse the effectiveness of current SLA with users’ perception on the cleanliness level. This study used qualitative and quantitative approaches. Content analysis and descriptive statistics were used for analysing the data. SLA for building cleaning documents were reviewed and 100 respondents were involved in this study. There are eighteen elements in the SLA documents. The result shows that current SLA is still effective. However, there are certain areas in and off the building that need to be improved such as the lecture room, parking lot and drains in terms of cleanliness. Furthermore, the decision to reduce the cost for refill tissues and hand soaps in the toilets does not satisfy the respondents. In conclusion, both of the outcomes contribute to the improvement of SLA for cleaning services as well as increase the quality of cleanliness level in UTHM.